Estudo da estabilidade da cirurgia do tipo sagital da mandíbula com vista a correção de deformidades faciais - Raldi, Fernando Vagner [UNESP] (1994)
This research evaluated the surgical stabilily in patients with mandibular prognathism and retrognathism in which was used sagital split technic to correct those detormities. Twelve patients were selected from the clinic of only one experienced surgeon. Six patients presenter a Class III 6 a Class II molar relationship. A comparative cefalometric analysis using linear and angular measurements was performed of pre-surgery, imediate pós-surgery and 1 year follow-up. The following conclusions were obtained. 1 The Dal Pont sagital split technic modified by Epker to correct mandibular prognathisn and retroghnatism is a stable technic and must be indicated to correct those deformities. 2 Small relapses are easily corrected by the post-surgical orthodontic treatment. 3 A small over correction is advised in cases of large mandibular advancements or set bascks. 4 In those cases which a large amount of mandibular retrusion on advancement need to be performed, a combination of maxillary and mandibular surgery should be used. Rigid fixation technic is also indicated in those cases